2022
DOI: 10.1186/s40364-022-00419-8
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction and ceRNA network of the tumor suppressor miR-637 in cancer development and prognosis

Abstract: MicroRNAs (miRNAs) are a class of small non-coding RNAs ranging from 17 to 25 nt in length. miR-637 is down-regulated in most cancers and up-regulated only in clear cell renal cell carcinoma (ccRCC). miR-637 can target 21 protein-coding genes, which are involved in the regulation of cell growth, cell cycle, cell proliferation, epithelial-mesenchymal transition (EMT), cancer cell invasion and metastasis, etc. In glioma, the transcription factor ZEB2 can bind to the miR-637 promoter region and inhibit miR-637 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…Subsequently, predictions from ceRNA networks combined with bioinformatic methods and luciferase reporter assays indicated that miR-637 could bind to circHIPK3 and FASN. So far, miR-637 has been shown to be involved in a variety of malignant behaviors [58,72,73]. For example, in triple-negative breast cancer, ectopic expression of miR-637 significantly attenuated the promotion of proliferation, migration, and invasion induced by upregulation of circSEPT9 in TNBC cells [73].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, predictions from ceRNA networks combined with bioinformatic methods and luciferase reporter assays indicated that miR-637 could bind to circHIPK3 and FASN. So far, miR-637 has been shown to be involved in a variety of malignant behaviors [58,72,73]. For example, in triple-negative breast cancer, ectopic expression of miR-637 significantly attenuated the promotion of proliferation, migration, and invasion induced by upregulation of circSEPT9 in TNBC cells [73].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, WNT3A-mediated activation of PI3K was demonstrated in colorectal cancer cells 69 . Additional connections between these pathways could be mediated by noncoding RNAs such as microRNAs or long noncoding RNAs 70 . Finally, stromal inflammation- and oxidative stress-induced genotoxicity and cell proliferation may promote cancer development through activation of NF-κB and PI3K/AKT signaling in epithelial cells 71,72 .…”
Section: Discussionmentioning
confidence: 99%
“…In the field of scientific research on NSCLC cells, the earlier research confirmed that adenocarcinoma‐specific miR‐181‐5p, miR‐361‐5p, and miR‐30a‐3p were certified to be promising and effective candidates for early diagnosis NSCLC 15 . As a crucial miRNA, miR‐637 was abnormally expressed in multiple of cancer cells, which was able to target 21 genes to take part in modulating cell growth 16 . Report from Teng et al verified that miR‐637 suppression was linked to TNM stage and poor prognosis of NSCLC patients and served as a tumor suppressor in NSCLC 17 .…”
Section: Introductionmentioning
confidence: 96%
“…15 As a crucial miRNA, miR-637 was abnormally expressed in multiple of cancer cells, which was able to target 21 genes to take part in modulating cell growth. 16 Report from Teng et al verified that miR-637 suppression was linked to TNM stage and poor prognosis of NSCLC patients and served as a tumor suppressor in NSCLC. 17 E2F2 is a normative transcription factor, which joins in transcription regulation, cell cycle, and tumorigenesis.…”
mentioning
confidence: 99%